Effect of silicide precipitation on tensile properties and fracture of alloy Ti-6Al-5Zr-0.5Mo-0.25Si - Ramachandra C.; Singh V. (My University, 2025)
The effect of silicon in solid solution and in the form of suicides has been studied on the tensile properties and fracture behavior of alloy Ti-6Al-5Zr-0.5Mo-0.25Si (alloy 685). The heat treatment to hold silicon in solid solution consists of solutionizing at 1323 K for 0.5 hour under vacuum (∼10-5 MPa), followed by water quenching, and the treatment to precipitate suicides involves subsequent aging of the solutionized and water quenched specimens at 1073 K for 24 hours. There is only marginal effect of the aging treatment on strength values; however, the ductility parameters are found to be drastically reduced. There are marked differences in the fracture behavior of the alloy in the as-quenched and the quenched and aged conditions. While the fracture surface of the unaged specimen shows characteristic dimples, there is a large number of facets on the fracture surface of the aged specimen. The facets in the central region are relatively smaller in size than those in the peripheral zone. The central facets show fluted features at higher magnifications; however, the peripheral facets are usually featureless. The faceted fracture in the aged condition is attributed to enhanced tendency for heterogeneous planar slip. The fracture characteristics correlate with the observed differences in the ductility in the two conditions. © 1985 The Minerals, Metals & Materials Society - ASM International - The Materials Information Society.